(untitled) (Sustainability in Debate, 2013)
In order to create the necessary scientific knowledge for Brazil to understand and deal with the causes and consequences of climate change, the federal government created, in 2007, the Brazilian Network on Global Climate Change Research (Rede CLIMA). Rede CLIMA needs to discuss issues, pose questions, develop methodologies and technological products, find answers, and suggest solutions that are relevant to society. In its first phase, it focused mainly on providing infrastructure and consolidating the sub-networks. Several scientific advances were also achieved, a selection of which are presented in sections focusing on climate modelling, agriculture, energy and water, human development and mobility, biodiversity and ecosystem services, and human health. Now, in its second phase, the objective is to straighten collaboration between sub-networks by means of interdisciplinary projects. It is argued that in order to succeed the Network needs to foster research whose merit is measured not exclusively by academic production.